Calculation of Mean Rainfall in Panjsher Province Using GIS - Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2021)
Rain and snow are the main types of precipitation, and rainfall is one of the most important variables determining the amount of water entering the subsystems of the hydrological cycle. Estimating average rainfall in different regions is crucial for addressing various hydrological problems. Precipitation data exhibit temporal and spatial variations, and it is inaccurate to assume that point precipitation represents a larger area. To relate point precipitation to larger areas, different mean methods must be used. This study aims to calculate the mean precipitation at several stations in Panjsher province using the Thiessen and Isohyetal methods, with the help of Geographic Information Systems (GIS).